Improvement of Leptospira spp. diagnosis in aborted bovine fetuses by qPCR - Cheuquepan Valenzuel, Felipe Andres (2020)
Leptospirosis is a disease with major economic impact on livestock industry. The objective of this work was to determine the presence of Leptospira spp. DNA by qPCR in bovine fetuses with presumptive diagnosis of leptospirosis as the cause of abortion. Leptospira spp. DNA was detected by qPCR in 11 out of 34 fetuses. These specimens (10/11) had histopathological findings in hepatic and/or renal tissues compatible with leptospirosis. qPCR detection rate (32.4 %) was higher compared with direct immuno-fluorescence antibody test (DFAT) (11.8 %). The concordance coefficient between both techniques was 0.44. qPCR is a rapid and sensitive technique for the diagnosis of leptospirosis and improved the detection rate in fetal tissues compared with DFAT. Implementation of molecular techniques may increase the accurate detection of leptospirosis as a cause of bovine abortion allowing the application of rapid therapeutic and prophylactics measures in order to reduce the impact of this zoonotic disease.